KANDUNGAN FENOL DAN LIGNIN TANAMAN NILAM HIBRIDA (Pogostemon sp.) HASIL FUSI PROTOPLAS - NURYANI, YANG; MUSTIKA, IKA; SYUKUR, CHEPPY (Jurnal Penelitian Tanaman Industri, 2001)
Evaluation of phenols and lignin in the root of hybrid patchouli (Pogostemon cablin Benth.) front protoplast fusionOne of the problems faced in patchouli production is nematode infection (Pratylenchus brachyurus). Improvement of the plant resistance to nematode in patchouli is dificult 10 be conducted through conventional method as the plant never llowcrs. One of the methods of improving (he plain resistance is by using protoplast fusion of Aceh patchouli (Pogostemon cablin, cv Sidikalang ) and Java patchouli (/' heyneanus. cv (iirilaya). It has been found thai Ihe plain resistance lo nematode is closely related to phenols and lignin content of the root Therefore. Ihe level of resistance of different clones of somatic hybrids lo nematode was approached by evaluating ihe content of phenols and lignin of the roots The study was conducted al the laboratory of the Research Institute for food Crop Biotechnology, Bogor in November 2000. Phenol content was determined with high performance liquid Chromatography (IIPI.C). while lignin content was determined with Klasou method. Result showed that Java patchouli (Girilaya) contained phenols and lignin respectively 76.53 and 21 900 pp. higher than those of Aceh patchouli (Sidikalang and Tapak Tuan) respectively 38 2-81 45 and 8 000-7 200 ppm. Phenol and lignin content in the somatic hybrids were dilferenl in Ihe respective pairs. In the fusion of Girilaya x Sidikalang. all clones contained phenol lower than those of Iheir parents, some clones (29%) contained lignin higher than Sidikalang but lower than (iirilaya. and the rest (71%) contained lignin lower than the two parents. Meanwhile, from Ihe fusion of Girilaya, Tapak Tuan. I clone (4%) contained phenols higher than those of (he two parents (97 ppm). 39% contained phenols higher than Tapak Tuan but lower than Girilaya (38.75-60.12 ppm) and the rests (60%) contained phenol lower than the two parents. Furthermore, the lignin content, of 78% somatic hybrids was lower than Girilaya but higher than Tapak Tuan, but the rest (22%) was lower than the two parents. Based on the distribution of phenols and lignin content. Ihe somatic hybrids can be categorized in three group The irst groups (5 clones) contained high phenols (higher than the average). Ihe second group (9 clones) contained high lignin. and Ihe third (I clone) contained high phenol and lignin.